Kutane Leishmaniasis als Reisedermatose. Klinik, Diagnostik und Therapie - Von Stebut, E.; Schleicher, Ulrike; Bogdan, Christian (Hautarzt, 2012)
Leishmaniasis is a disease with worldwide increasing incidence, which in Germany is almost exclusively observed in patients who have travelled to classical endemic regions such as the Mediterranean basin. Cause of the disease is an infection with protozoan parasites of the genus Leishmania, which are transmitted by sand flies and replicate intracellularly within mammalian hosts. Depending on the inoculated parasite (sub-) species and the immune status of the host, a local cutaneous, diffuse cutaneous, mucocutaneous or visceral form of leishmaniasis will develop. Cutaneous leishmaniasis, which frequently appears only weeks after the bite of a sand fly, starts with the formation of a papule, which subsequently can turn into a skin ulcer. The latter may heal spontaneously after months leaving behind a scar or persist as chronic, non-healing cutaneous leishmaniasis. If cutaneous leishmaniasis is suspected, a sterile skin biopsy followed by appropriate diagnostic measures in a specialized laboratory to identify the pathogen should be performed. For the decision on the type of therapy, several clinical parameters (e.g. number and localization of lesions, immune status) and, most importantly, the underlying parasite (sub-) species need to be considered. Therapy can consist of a variety of topical measures or systemic drug treatment. A modern and safe vaccine does not yet exist. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Cutaneous leishmaniasis; Leishmaniasis; Mucocutaneous leishmaniasis; Oriental sore; Therapy